2021
DOI: 10.1055/s-0040-1721199
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus Oil-Induced Seizures in Children: Case Reports and Review of the Literature

Abstract: Objective Eucalyptus oil (EO)-induced seizures (EOIS) in children is a less recognized entity and a rare cause of acute symptomatic seizures. The purpose of this review outlines the clinical features and outcomes of EOIS with observed cases. Patients and Methods We identified three pediatric patients with EOIS who were treated at Prathima Institute of Medical Sciences, Karim Nagar, India. Results Seizures were developed in three children within 15 to 25 minutes after the ingestion of EO. All the children have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The higher good knowledge in health personnel 8.8% compared to parents 0.3% can be accounted for by the number of years of studies and years in practice of health personnel. This goes in line with two studies conducted in India and published in 2021 by Chandar Dudipala et al which revealed that despite the previous case reports in the literature quoting the seizurogenic potential of EO, this awareness was lacking in both clinicians and parents and that the knowledge about EO induced-seizures was essential to be disseminated among health care professionals and the general population [3,10]. 94.0% parents strongly agreed on the fact that self-medication by parents on children could bring about negative effects like convulsions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The higher good knowledge in health personnel 8.8% compared to parents 0.3% can be accounted for by the number of years of studies and years in practice of health personnel. This goes in line with two studies conducted in India and published in 2021 by Chandar Dudipala et al which revealed that despite the previous case reports in the literature quoting the seizurogenic potential of EO, this awareness was lacking in both clinicians and parents and that the knowledge about EO induced-seizures was essential to be disseminated among health care professionals and the general population [3,10]. 94.0% parents strongly agreed on the fact that self-medication by parents on children could bring about negative effects like convulsions.…”
Section: Discussionsupporting
confidence: 83%
“…of the Myrtaceae family and is rich in 1,8-cineole (eucalyptol) [2]. It is an expectorant used in pharmaceutical products against cough, common cold and bronchitis [1,3]. Camphorated oil and Eucalyptus essential oil (EO) can cause poisonings [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining 32 articles, 15 satisfied all the inclusion criteria for our review. 519 Out of these, three were prospective observational studies, three retro-spective studies or case record reviews, six small case series and three single case reports.
Figure 1.Flow diagram of the study selection process.
…”
Section: Resultsmentioning
confidence: 99%